Interpersonal Meaning in Instagram Captions: a Discourse Analysis of the Instagram Account @kopikenangan.id - Nur Hanifatul Zakiyah (Journal of Social Research, 2025)
This study analyzed the interpersonal meaning in the caption of the Instagram account @kopikenangan.id using the framework of Systemic Functional Linguistics and Discourse Analysis. The goal is to identify the linguistic forms and discourse strategies that brands use to build social proximity to their audiences. Descriptive qualitative data in the form of ten captions were analyzed based on elements of mood, modality, and pronouns. The results show the dominance of declarative sentence structures that function informatively while affirming the brand image of a friendly and nationalist brand. In addition, it was found that the use of imperative sentences that are inviting and familiar, which is strengthened by positive modalities such as can and should. Inclusive pronouns (we, us, you) and typical greetings (Ex-Men) are key strategies to eliminate social distancing and create emotional and participatory connections. Overall, Kopi Kenangan captions utilize language as a social practice to construct a friendly and inclusive brand identity in the digital space.